2006
DOI: 10.1002/app.24390
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol‐β‐cyclodextrin) gels: Synthesis and properties

Abstract: A new hydrogel that combines poly(ethylene glycol) and b-cyclodextrin has been synthesized. Both components are linked by using a diisocyanate (HDMI), first by end-capping the poly(ethylene glycol) with isocyanate groups an then reacting it with b-cyclodextrin, forming urethane links. Hydrogels of molar compositions (b-cyclodextrin/poly(ethylene glycol)) ranging from 1/4 to 1/14 have been synthesized. These hydrogels swell quickly and their water contents depend upon temperature. The gels are temperature resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 19 publications
4
45
0
Order By: Relevance
“…This fact, coupled with its chemical and thermal stability, and good mechanical properties, as has been reported in previous works 8,9 makes them interesting materials for removing organic contaminants from water. Number: MAT2010-21509-CO3) and Gobierno Vasco (Grupos consolidados) to whom researches are gratefully acknowledged.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…This fact, coupled with its chemical and thermal stability, and good mechanical properties, as has been reported in previous works 8,9 makes them interesting materials for removing organic contaminants from water. Number: MAT2010-21509-CO3) and Gobierno Vasco (Grupos consolidados) to whom researches are gratefully acknowledged.…”
Section: Resultssupporting
confidence: 59%
“…Recently, our group has developed a new type of hydrogels containing -CD by using as crosslinking agent a modified Poly(ethylene glycol) (PEG): poly(ethylene glycol) end-capped with a diisocyanate 8,9 . The reaction between the chains of the modified PEG and the hydroxyl groups of cyclodextrin rings leads to the formation of a network with urethane bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions cyclodextrins can form inclusion complexes in aqueous media capturing diverse substances or can be applied in drug delivery when it is loaded, allowing easy recovery and recycling. In a previous study, [11] we have shown that poly (ethylene glycol) (PEG) chemically modified by coupling with diisocyanates can be cross-linked with b-cyclodextrin (b-CD). These gels have been prepared by using b-cyclodextrin molecules as cross-linking agent for poly(ethylene glycol) chains (molar mass ¼ 600 g Á mol…”
Section: Introductionmentioning
confidence: 99%
“…The weight losses below 250 C were caused by the elimination of the physically adsorbed water from X-CD_3.9_0.78. 39 The amorphous nature of X-CD_3.9_0.78 was also confirmed by diminish of characteristic peaks of β-CD in Figure 4(c). It is worth mentioning that an increase of the thermal resistance of X-CD_3.9_0.78 occurred with regard to the b-PEI, PEG, and β-CD, which is typical of crosslinked polymers.…”
Section: Characterization Of X-cdmentioning
confidence: 65%